LEFT VENTRICULAR WALL THICKNESS AND AUTONOMIC REGULATION IN PATIENTS WITH HYPERTROPHIC CARDIOMYOPATHY - O. Allaberganov; T. A. Abdullaev; G. A. Nagaeva (Российский кардиологический журнал, 2011)
The study included 21 patients (mean age 35,86±10,01 years) with hypertrophic cardiomyopathy (HCMP) diagnosed according to the WHO criteria. All patients underwent in-hospital complex clinical and functional assessment, electrocardiography (QT dispersion, Sokolow-Lyon index, and Cornell voltage index analysis), Holter ECG monitoring (time and spectral parameter analysis), and echocardiography (EchoCG). Based on the interventricular septum thickness (IVST), all patients were divided into two groups: Group I with IVST <20 mm (n=13) and Group II with IVST >20 mm (n=8). Group II was characterised by left ventricular diastolic dysfunction, with a tendency towards the development of its restrictive variant. In addition, Group II patients demonstrated autonomic disbalance, sympathetic hyperactivity, and disturbed circadian patterns of heart rate.